12‐Month progression of motor and functional outcomes in congenital myotonic dystrophy. Issue 3 (10th January 2021) - Quigg, Kellen H.; Berggren, Kiera N.; McIntyre, Melissa; Bates, Kameron; Salmin, Francesca; Casiraghi, Jacopo L.; DʼAmico, Adele; Astrea, Guja; Ricci, Federica; McKay, Marnee J.; Baldwin, Jennifer N.; Burns, Joshua; et al.
Abstract: Background: We aim to describe 12‐mo functional and motor outcome performance in a cohort of participants with congenital myotonic dystrophy (CDM). Methods: CDM participants performed the 6 Minute Walk Test (6MWT), 10 Meter Run, 4 Stair Climb, Grip Strength, and Lip Force at baseline and 12‐mo visits. Parents completed the Vineland Adaptive Behavior Scale. Results: Forty‐seven participants, aged 0 to 13 y old, with CDM were enrolled. 6MWT, 10 Meter Run, and 4 Stair Climb were completed in >85% of eligible participants. The only significant difference between mean baseline and 12‐mo performance was an improvement in 6MWT in children 3‐6 y old ( P = .008). This age group also had the largest mean % improvement in performance in all other timed functional testing. In children >7 y, the slope of change on timed functional tests decreased or plateaued, with further reductions in performance in children ≥10 y. Participants with CTG repeat lengths <500 did not perform differently than those with repeat lengths >1000. Conclusions: The 6MWT, 10 Meter Run, and 4 Stair Climb were the most feasible measures. Our findings are consistent with the clinical profile and prior cross‐sectional data, helping to establish reasonable expectations of functional trajectories in this population as well as identifying points in which therapeutic interventions may be best studied. Further study of outcomes in children >10 y old and <3 y is warranted, but this new information will assist planning of clinical trials in the CDM population.